Should strategies benefit the difficult or the more favoured environments? - Treitz, Werner (Technical Centre for Agricultural and Rural Cooperation, 1989)
Dr WERNER TREITZ Dr Wemer Treitz has been CTA's Deputy Director since 1983. Before jioning CTA he spent nearly twenty years at the German Federal Ministry for Economic Cooperation (BMZ) in Bonn. One of his major functions at BMZ was to head the...